Arboreal Imagination in Kalidasa's Abhijnanashakuntalam: Reimagining Trees as Sentient Agents through the Lens of Plant Humanities (Rupandehi Campus Journal, 2025)
This study examines ecological consciousness in Kalidasa’s Abhijnanashakuntalam, highlighting the active role of plants in the narrative. Drawing on frameworks such as Michael Marder’s Plant Thinking and Matthew Hall’s concept of plant personhood, it shows how Kalidasa attributes symbolic, emotional, and spiritual agency to trees within Shakuntala’s forest hermitage. Arboreal characters like the mango tree and jasmine vine act as emotional mediators and narrative participants, reflecting ancient Indian ecological awareness. The study bridges classical Sanskrit literature with modern environmental thought, arguing that Kalidasa’s work anticipates the themes of plant humanities and reveals deep interconnections between humans and nature in literary imagination.